Effects of repetitive transcranial magnetic stimulation on cognitive function and hormone levels in early stroke patients with low thyroid hormone levels - Li, Hong; Ma, Jiang; Song, Ziqiang; Tao, Xiaolin; Xing, Yan; Zhang, Feng (Frontiers in Aging Neuroscience, 2024)
Background: This study aimed to observe the effects of repetitive transcranial magnetic stimulation (rTMS) on cognitive function and thyroid hormone levels in early older stroke patients with low thyroid hormone levels, and to investigate the correlation between the changes in thyroid hormone levels and the improvements in cognitive function after stroke. scores in the rTMS group were statistically higher than those in the Sham group at the end of the 4-week intervention and at the follow-up (P<0.05); The changes in the levels of T3 before and after 4-week intervention were positively correlated with the changes in the MoCA scores (r=0.638, P<0.05). And the difference in T3 level change was positively correlated with the difference in delayed recall, attention and naming score change (r=0.562, P<0.05; r=0.562, P<0.05; r=0.531, P<0.05); and the difference in FT3 level change was positively correlated with the visuospatial and executive function (r=0.514, P<0.05). Conclusion: Repetitive transcranial magnetic stimulation improved cognitive function and elevated T3 levels in older patients with post-stroke cognitive dysfunction who had low thyroid hormone levels. Within the normal range, increases in T3 levels are positively correlated with changes in cognitive function.